Uwagi w sprawie uzyskiwania opinii o stanie zdrowia psychicznego sprawców przestępstw w toku postępowania karnego - Pachnik, Karol; Ring, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Current Polish legislation demands to appoint at least two court experts — psychiatrists which are appointed to evaluate the state of mental health of the accused and in specific cases to include a sexologist in the team of experts. The present knowledge allows to draw a conclusion that very often it is necessary to include in the team of court experts specialists from other fields, for example a psychologist or a sociologist. The authors of this article consider the possibility of including in the team of court experts also persons who evaluate the state of mental health in different areas.
Keywords: opiniowanie; biegli sądowi - psychiatrzy; stan zdrowia psychicznego; niepoczytalność